Digital Game-Based Learning Interventions on Students' Numeracy Skills and Engagement - Sari, Nenden Mutiara; Yaniawati, Poppy; Supianti, In In; Indriani, Rina (Formatif: Jurnal Ilmiah Pendidikan MIPA, 2025)
Numeracy skills play a crucial role in various aspects of life, both in mathematical learning and in daily life. Numeracy is the key to understanding and mastering various mathematical concepts. However, several research findings indicate that these skills are still relatively low. The low numeracy skills are attributed to the low engagement of students in mathematical learning. When students feel actively engaged in learning, they tend to be more motivated to learn and better able to understand the concepts taught. One effort to engage students in learning activities is by interestingly presenting learning content. Digital game-based learning is expected to improve numeracy skills and student engagement in mathematical learning. This study is a mixed-method research. The participants in this study were fourth-grade elementary school students divided into two groups: the experimental group and the control group. The instruments used were numeracy ability tests and observation sheets. The results of the study indicate that (1) the numeracy skills of students who received digital game-based learning are better than those of students who received traditional learning; (2) there are differences in the mean numeracy skills of students based on the intensity of playing games; and (3) Student engagement in digital game-based learning is classified as very high.